Partial Detachment of the Gluteus Maximus Muscle to Expose the Proximal Third of the Sciatic Nerve in the Infragluteal Approach: An Alternative Technique to Minimize Iatrogenic Muscle Deafferentation Damage - Gagliardi, Filippo; De Domenico, Pierfrancesco; Ometti, Marco; Mandelli, Carlo; Colombo, Elena Virginia; Mortini, Pietro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Exposing the proximal extrapelvic sciatic nerve usually requires a partial transsection of the gluteus maximus muscle. The authors describe a modified infragluteal technique for mobilizing the gluteus maximus muscle, with only partial detachment of the muscle aponeurosis attaching to the femur.An illustrative case is reported to demonstrate the surgical feasibility of the approach. The present technique offers good operability, with only a slight decrease in the angle of the surgical corridor compared with the standard infragluteal and transgluteal techniques, while preventing muscle damage resulting from muscle deafferentation.
Keywords: approach; infragluteal; sciatic nerve; schwannoma; gluteus maximus